Adipocyte‐Derived Exosomal MTTP Suppresses Ferroptosis and Promotes Chemoresistance in Colorectal Cancer. Issue 28 (17th August 2022) - Zhang, Qiumo; Deng, Ting; Zhang, Hongdian; Zuo, Duo; Zhu, Qihang; Bai, Ming; Liu, Rui; Ning, Tao; Zhang, Le; Yu, Zhentao; Zhang, Haiyang; Ba, Yi
Abstract: Obesity is closely related to a poor prognosis in patients with advanced colorectal cancer (CRC), but the mechanisms remain unclear. Ferroptosis is a form of nonapoptotic cell death characterized by lipid reactive oxygen species (ROS) accumulation and iron dependency and is associated with the chemoresistance of tumors. Here, it is shown that adipose‐derived exosomes reduce ferroptosis susceptibility in CRC, thus promoting chemoresistance to oxaliplatin. It is found that microsomal triglyceride transfer protein (MTTP) expression is increased in the plasma exosomes of CRC patients with a high body fat ratio, serving as an inhibitor of ferroptosis and reducing sensitivity to chemotherapy. Mechanistically, the MTTP/proline‐rich acidic protein 1 (PRAP1) complex inhibited zinc finger E‐box binding homeobox 1 expression and upregulated glutathione peroxidase 4 and xCT, leading to a decreased polyunsaturated fatty acids ratio and lipid ROS levels. Moreover, experiments are carried out in organoids, and a tumor implantation model is established in obese mice, demonstrating that the inhibition of MTTP increases the sensitivity to chemotherapy. The results reveal a novel intracellular signaling pathway mediated by adipose‐derived exosomes and suggest that treatments targeting secreted MTTP might reverse oxaliplatin resistance in CRC. Abstract : The authors show that adipose‐derived exosomes reduce ferroptosis susceptibility in CRC, thus promoting chemoresistance to oxaliplatin. MTTP expression is increased in the plasma exosomes of CRC patients with a high body fat ratio, leading to a decreased polyunsaturated fatty acid (PUFA) ratio and lipid ROS levels, which serving as an inhibitor of ferroptosis and reducing sensitivity to chemotherapy.